The New Turn to Mecca - Michael Laffan (Revue des Mondes Musulmans et de la Méditerranée)
Taking the extensive Java notebooks of Christiaan Snouck Hurgronje (1857-1936) as a lens, this essay discusses the globalising forms being adopted in Java’s Islamic schools in the late nineteenth century. Snouck Hurgronje’s notes reveal a self-conscious transition towards the consumption of printed Arabic sources away from the use of older indigenous manuscript glossings of the same corpus. This shift came in tandem with the rising popularity of certain Sufi brotherhoods headquartered at Mecca, most particularly the Naqshbandiyya, which readily adopted print for the dissemination of their litanies and manuals. I will close by suggesting that, in the long run, it was this shift that would make possible the later arrival of “Islamic modernism” in the ports of the archipelago, against which the Islam documented by Snouck Hurgronje would ultimately be juxtaposed as a rural, anti-modern, and “traditional” survival of past ages.